Investigating the relationship between sexual intimacy, emotion regulation and attachment styles - Akhavan Kharazi, Maryam; Ramezani, Mohammad Arash (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and objective: Marriage is an intimate relationship with authority and is undergoing transformation, therefore intimacy in marriage is different from the type of relationship experienced between mother and child. The purpose of this research is to investigate the relationship between sexual intimacy, emotion regulation and attachment dimensions in married people. Methods: The research method is cross-sectional correlation. The statistical population of the current study includes all married men and women living in Tehran province, which was selected using available sampling method. The data were obtained using the close relationship experience questionnaire (Brennen, Clark and Shaver, 1998), the cognitive regulation of emotion questionnaire (Garnefsky, Kraij and Spinhaven, 2002) and Bagaroosi’s intimacy needs questionnaire (2001). The data were analyzed by mean, standard deviation, correlation coefficient and multivariate regression and SPSS 21 and AMOS statistical software. Results: The results showed that there is a significant relationship between the dimensions of anxious attachment and intensity of sexual need (r=0.167, P<0.01) and sexual participation (r=0.157, P<0.01) in married people. There is. The relationship between the dimensions of avoidant attachment and sexual intimacy in the sexual need satisfaction component was significant (p<0.01, r=0.155). The correlation between anxiety style and negative emotional regulation strategies was significant (r=0.132). But there was a significant correlation between the dimension of avoidant attachment and positive emotional regulation (r=0.237). Sexual intimacy and positive emotional regulation were also related (r=0.174). Conclusion: It can be concluded that both dimensions of attachment are correlated with sexual intimacy, but there is no significant correlation between emotional regulation and attachment styles.